The Contribution and Potential of Data Harmonization for Cross-National Comparative Research - Richard V. Burkhauser; Dean R. Lillard (Deutsches Institut für Wirtschaftsforschung (DIW), 2005)
The promise of empirical evidence to inform policy makers about their population?s health, wealth, employment and economic well being has propelled governments to invest in the harmonization of country specific micro data over the last 25 years. We review the major data harmonization projects launched over this period. These projects include the Luxembourg Income Study (LIS), the Cross-National Equivalent File (CNEF), the Consortium of Household Panels for European Socio-Economic Research (CHER), the European Community Household Panel (ECHP), the European Union Statistics on Income and Living Conditions (EU-SILC), and the Survey of Health, Aging and Retirement in Europe (SHARE). We discuss their success in providing reliable data for policy analysis and how they are being used to answer policy questions. While there have been some notable failures, on the whole these harmonization efforts have proven to be of major value to the research community and to policy makers.
Keywords: 330